2002
DOI: 10.1083/jcb.200110045
|View full text |Cite
|
Sign up to set email alerts
|

The aurora kinase AIR-2 functions in the release of chromosome cohesion in Caenorhabditis elegans meiosis

Abstract: Accurate chromosome segregation during cell division requires not only the establishment, but also the precise, regulated release of chromosome cohesion. Chromosome dynamics during meiosis are more complicated, because homologues separate at anaphase I whereas sister chromatids remain attached until anaphase II. How the selective release of chromosome cohesion is regulated during meiosis remains unclear. We show that the aurora-B kinase AIR-2 regulates the selective release of chromosome cohesion during Caenor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
241
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(266 citation statements)
references
References 59 publications
(94 reference statements)
23
241
1
1
Order By: Relevance
“…It is intriguing that the passenger proteins are not detected in the centromere regions as they are in mitotic and centrosomal meiotic cells. Our results are consistent with data from C. elegans oocytes (Kaitna et al 2002;Rogers et al 2002;Monen et al 2005) and mouse oocytes (Shuda et al 2009;Sharif et al 2010), showing that the CPC interacts with noncentromeric chromatin at metaphase of meiosis I. In C. elegans, the CPC forms a ring at the center of each bivalent that colocalizes with cohesion proteins distal to chiasmata Figure 6 Model for the relationship between the central spindle, spindle bipolarity, and centromere orientation during acentrosomal spindle assembly.…”
Section: Cpc Promotes Spindle Assembly and Establishes The Spindle Axissupporting
confidence: 88%
See 2 more Smart Citations
“…It is intriguing that the passenger proteins are not detected in the centromere regions as they are in mitotic and centrosomal meiotic cells. Our results are consistent with data from C. elegans oocytes (Kaitna et al 2002;Rogers et al 2002;Monen et al 2005) and mouse oocytes (Shuda et al 2009;Sharif et al 2010), showing that the CPC interacts with noncentromeric chromatin at metaphase of meiosis I. In C. elegans, the CPC forms a ring at the center of each bivalent that colocalizes with cohesion proteins distal to chiasmata Figure 6 Model for the relationship between the central spindle, spindle bipolarity, and centromere orientation during acentrosomal spindle assembly.…”
Section: Cpc Promotes Spindle Assembly and Establishes The Spindle Axissupporting
confidence: 88%
“…(E) A pathway for biorientation. (Rogers et al 2002;Wignall and Villeneuve 2009). The C. elegans CPC ring is a complex structure that, as in Drosophila, contains motor proteins (Klp-19) (Powers et al 2004) and is required for segregation of homologs at meiosis I (Wignall and Villeneuve 2009;Dumont et al 2010).…”
Section: Cpc Promotes Spindle Assembly and Establishes The Spindle Axismentioning
confidence: 99%
See 1 more Smart Citation
“…The -1 oocyte in hermaphrodites spends $23 min in the most proximal position and in the final 3-6 min will undergo the meiotic maturation events of nuclear envelope breakdown (NEBD) and cortical rearrangement (McCarter et al 1999; Figure 6). During this period, the initially dispersed diakinesis bivalents of the -1 oocyte congress to the metaphase plate, chromosomal AIR-2 aurora kinase staining increases from low to high and metaphase I (MI) spindle formation begins (Figure 4, B and C; Schumacher et al 1998;Rogers et al 2002;Yang et al 2003). We found that in $15% of -1 oocytes dpMPK-1 is very low/undetectable (Figure 4, A and C).…”
Section: Resultsmentioning
confidence: 80%
“…Although the CPC localizes to the midzone during anaphase in oocytes, its function in assembling this structure has not been examined carefully in most species or is obscured by earlier essential functions such as chromosome cohesion, as is the case in C. elegans oocytes [Kaitna et al, 2002;Rogers et al, 2002;Dumont et al, 2007a]. Nevertheless, impairing CPC function in oocytes prevents PBE, which suggests that its roles are conserved between mitotic and meiotic cytokinesis [Kaitna et al, 2002;Rogers et al, 2002;Sharif et al, 2010;Yang et al, 2010].…”
Section: The Spindle Midzone: a Hub For Cytokinesis Regulationmentioning
confidence: 99%